Incidence, Clinical Manifestations, and Severity of Juvenile Idiopathic Arthritis Among Maori and Pacific Island Children. Issue 9 (3rd August 2019) - Concannon, Anthony; Reed, Peter; Ostring, Genevieve
Abstract : Objective: To describe the incidence, demographics, diagnostic clinical manifestations, and severity of juvenile idiopathic arthritis (JIA) in Maori and Pacific Island children compared to European children. Methods: A chart review was conducted of all children with JIA seen by Auckland pediatric and rheumatology services between the years 2000 and 2015. Demographic data and diagnostic clinical manifestations, including poor prognostic features, were collated. The incidence, diagnostic, clinical manifestations, and severity of JIA were determined and compared between ethnic groups, in particular Maori, Pacific Island, and European children. Results: The overall incidence in a New Zealand cohort of children with JIA was 5.1/100, 000 children per year, which was significantly higher among European children (7.2/100, 000 children per year) compared to all other ethnic groups. Poor prognostic features at diagnosis were present in 36% of children with JIA, with significantly more Maori and Pacific Island children presenting with poor prognostic features compared to European children (58% versus 27%; P = 0.0001). Maori and Pacific Island children had significantly more poor prognostic features per child associated with JIA (1.10 versus 0.37; P < 0.0001) and in oligoarticular and polyarticular JIA (1.28 versus 0.40; P < 0.0001), which was independent of socioeconomic status. Significant features included cervical involvement (25% versus 9%; P = 0.03), erosive changes (22% versus 8%; P = 0.05), joint space narrowing (13% versus 2%; P = 0.02), and positive rheumatoid factor polyarticular disease (47% versus 14%; P = 0.01). Conclusion: Maori and Pacific Island children were more likely to present with poor prognostic features at diagnosis, although the incidence of JIA was demonstrated to be significantly higher among European children compared to all ethnic groups.